Tracking of structural defects induced by Eu-doping in β-Ag2MoO4: their influences on electrical properties - Macchi, Carlos; Petinardi, Guilherme Magalhaes; Freire, Leonardo Almeida; Castro, Miriam Susana; Aldao, Celso Manuel; Luiz, Thaís Marcial; Moura, Francisco; Simões, Alexandre Zirpoli [UNESP]; Moreno, Henrique [UNESP]; Longo, Elson; Somoza, Alberto; Assis, Marcelo; et al. (Royal Society of Chemistry (RSC), 2023)
In this study, several methods were employed to investigate the electrical characteristics of β-Ag2MoO4 systems, both Eu-doped and undoped, synthesized using the microwave-assisted hydrothermal method. The focus extended to understanding how synthesis time influences material defects, with doping fixed at 1%. A systematic shift in the silver vacancy (VAg) concentration was observed within the doped β-Ag2MoO4 system. Specifically, this study demonstrated that the incorporation of Eu3+ into polycrystalline β-Ag2MoO4 initially increases the VAg concentration. However, as the synthesis time progresses, the VAg concentration decreases, resulting in alterations in the resulting electrical properties, arising from the intricate interplay between the number of grain boundaries and carrier density. By combining information obtained from photoluminescence, positron annihilation lifetime spectroscopy, and impedance spectroscopy, a comprehensive conduction mechanism was formulated, shedding light on both doped and undoped β-Ag2MoO4 systems.